Pengembangan Desa Sentral Kakao Berkelanjutan Melalui Penerapan Good Agriculture Practices (GAP) - Muhammad Ghufron Rosyady; Gatot Subroto; Dyah Ayu Savitri; Setiyono Setiyono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Jambewangi Village is a village that is one of the focus locations for cocoa plantations according to the Banyuwangi Regency Agriculture Service. Cocoa production in Jambewangi Village is around ±500 kg/ha in 2019, far from the potential for superior cocoa production of ±2,000 kg/ha. The problem in Jambewangi Village is that cocoa plants are not the main crop in Jambewangi Village, this is because cocoa plants do not provide optimal benefits for the community (low productivity). Whereas Jambewangi Village is one of the people's cocoa centers in Banyuwangi Regency. When the service team conducted initial observations and interviews with Jambewangi cocoa farmers, several problems were found, namely that many cocoa pods were rotten by the fungus Phithopthora; leaves and fruit with lots of spots (attacked by Helopeltis pests), the condition of the garden is dirty and lush; and no rorak in the garden. This problem arises because farmers do not apply good and correct cultivation practices (GAP). The implementation of GAP will increase the productivity of cocoa plants, increasing productivity will improve the welfare of the Jambewangi community. The socialization program and the practice of implementing Good Agriculture Practices (GAP) for cocoa plants provide a stimulus to farmers to apply it in cocoa cultivation activities so that it is hoped that this can be a step to develop local potential and the surrounding community. Farmers in Jambewangi Village showed high enthusiasm for mastering the application of Good Agriculture Practices (GAP) including fertilizing, pruning and making rorak.